Case of Self-Mutilation –Lesch-Nyhan Syndrome - Gupta, Sweta Kumari; Dallakoti, Samanata; Sapkota, Ranjit; Sangroula, Niraj (Journal of College of Medical Sciences-Nepal, 2022)
Lesch-Nyhan syndrome involves a congenital error of purine metabolism, due to the absence (or very low levels) of hypoxanthine-guanine phosphoribosyltransferase (HPRT) enzyme. The classic clinical phenotype of LNS was first described by Michael Lesch and William Nyhan in 1964 and is characterized by hyperuricemia, intellectual disability, severe motor deficiency, and recurring self-mutilation . Here we present a case of a 4-year-old male child with features of self-mutilation, aggression, and poor neck control and unable to sit and stand. we diagnosed him as a case of Lesch-Nyhan syndrome based on clinical features and slight hyperuricemia. Due to the lack of medical facilities, many cases of Lesch-Nyhan syndrome undergo unnoticed in many underdeveloped countries.